Hubungan antara Keterampilan Komunikasi dengan Aktivitas Belajar Siswa - Maryanti, Silya; Zikra, .; Nurfarhanah, . (Universitas Negeri Padang, 2012)
Abstract, Problems that occur in the field is that there are some students who do not communicate well skilled in the learning activities so that learning results are obtained not maximized. The purpose of this study was (1) Describe the communication skills of students SMAN 2 South Solok, (2) Describe the student learning activities SMAN 2 South Solok, (3) Looking relationship communication skills with students' learning activities SMAN 2 South Solok. This study uses quantitative correlational descriptive analysis approach.